Resiliensi Sosial pada Anak Single Parent Usia Dasar - Shofi Nur Amalia (Journal on Education, 2023)
The stigma of today's society always looks down on children who are raised by single parents. Various negative assumptions often arise, such as children who are raised by single parents have deviant behavior. However, in this study, examples of cases were found if in the world of psychology, including real cases is unique and rare. Because single parent children in this study were able to prove to the public that their attitudes and behavior were not like the general theory. Her responsive and independent attitude can be used as a role model for children her age. This is because the parenting style of the subject's mother is very serious in educating her child. In addition to the parenting style of the parents, there are several other factors that support the formation of the child's character. Such as the neighborhood where she lives, friends in everyday life and the school where she studies. So in this study it was found that children from single parent parenting did not always have deviant behavior. Although it is very minimal to get parental supervision, the subject has high social resilience to herself and others.